Maine’s Congressional Delegation Reflections on Our Shared Ocean - Collins, Susan; King, Angus; Pingree, Chellie; Golden, Jared (Maine Policy Review, 2023)
Maine Policy Review submitted a series of questions to Maine’s Congressional Delegation to get their take on issues confronting “Our Shared Ocean” and the public policies they are engaged in to ensure Maine’s coast and ocean and their associated livelihoods remain protected for future generations.